Safety, immunogenicity, and preliminary clinical efficacy of a vaccine against extraintestinal pathogenic Escherichia coli in women with a history of recurrent urinary tract infection: a randomised, single-blind, placebo-controlled phase 1b trial. Issue 5 (May 2017) - Huttner, Angela; Hatz, Christoph; van den Dobbelsteen, Germie; Abbanat, Darren; Hornacek, Alena; Frölich, Rahel; Dreyer, Anita M; Martin, Patricia; Davies, Todd; Fae, Kellen; van den Nieuwenhof, Ingrid; Thoelen, Stefan; et al.
Summary: Background: Escherichia coli infections are increasing worldwide in community and hospital settings. The E coli O-antigen is a promising vaccine target. We aimed to assess the safety and immunogenicity of a bioconjugate vaccine containing the O-antigens of four E coli serotypes (ExPEC4V). Methods: In this multicentre phase 1b, first-in-human, single-blind, placebo-controlled trial, we randomly assigned (1:1) healthy adult women with a history of recurrent urinary tract infection (UTI) to receive a single injection of either intramuscular ExPEC4V or placebo. The primary outcome was the incidence of adverse events among vaccine and placebo recipients throughout the study. Secondary outcomes included immunogenicity and antibody functionality, and the incidence of UTIs caused by E coli vaccine serotypes in each group. This study is registered withClinicalTrials.gov, numberNCT02289794 . Findings: Between Jan 20, 2014, and Aug 27, 2014, 93 women received target-dose ExPEC4V and 95 received placebo. The vaccine was well tolerated: no vaccine-related serious adverse events occurred. Overall, 56 (60%) target-dose vaccines and 47 (49%) placebo recipients experienced at least one adverse event that was possibly, probably, or certainly related to injection. Vaccination induced significant IgG responses for all serotypes: at day 30 compared with baseline, O1A titres were 4·6 times higher, O2 titres were 9·4 times higher, O6A titres were 4·9 times higher, and O25B titres were 5·9 times higher (overall p<0·0001). Immune responses persisted at 270 days but were lower than those at 30 days. Opsonophagocytic killing activity showed antibody functionality. No reduction in the incidence of UTIs with 10 3 or more colony-forming units per mL of vaccine-serotype E coli was noted in the vaccine compared with the placebo group (0·149 mean episodes vs 0·146 mean episodes; p=0·522). In post-hoc exploratory analyses of UTIs with higher bacterial counts (≥10 5 colony-forming units per mL), the number of vaccine serotype UTIs did not differ significantly between groups (0·046 mean episodes in the vaccine group vs 0·110 mean episodes in the placebo group; p=0·074). However, significantly fewer UTIs caused by E coli of any serotype were noted in the vaccine group compared with the placebo group (0·207 mean episodes vs 0·463 mean episodes; p=0·002). Interpretation: This tetravalent E coli bioconjugate vaccine candidate was well tolerated and elicited functional antibody responses against all vaccine serotypes. Phase 2 studies have been initiated to confirm these findings. Funding: GlycoVaxyn, Janssen Vaccines.